The Values of Moral Education in Buya Hamka's Thought and Its Application to Students of Grade VIII SMP Muhammadiyah 5 Surakarta - Barr, Muhammad Abdel; Wibowo, Muhammad Kurniawan Budi; Abbas, Ngatmin (PALAPA, 2025)
This study is driven by the scarcity of research on the application of Buya Hamka’s concept of moral education within formal educational settings, despite its significant influence on adolescent moral development. The research aims to analyze the implementation of Buya Hamka’s moral values among Grade VIII students at SMP Muhammadiyah 5 Surakarta and to identify the supporting and inhibiting factors influencing this process. Employing a qualitative case study approach, the study involved purposively selected participants, including the principal, teachers, homeroom teachers, and students. Data were collected through observation, in-depth interviews, and documentation, and analyzed thematically. The findings indicate that the internalization of moral values is manifested through the habituation of religious worship, the role-modeling of teachers, and structured religious programs that promote the virtues of wisdom (ḥikmah), self-restraint (‘iffah), courage (shajā‘ah), and justice (‘adl). Supporting factors include teacher exemplarity, parental involvement, and a conducive religious environment, while inhibiting factors comprise the lack of value reinforcement at home and negative influences from social media. The study affirms the continued relevance of Buya Hamka’s moral philosophy in addressing contemporary challenges in character education.